ROLE OF WALI, ANCIENT MOSQUE AND SACRED TOMB IN ISLAM SPREADING DYNAMICS IN CIKAKAK - arnis rachmadhani (IBDA` : Jurnal Kajian Islam dan Budaya, 2016)
AbstractThis qualitative research was conducted in the Islamic communities who base all its activities on Aboge calendar calculations in the village of Cikakak,Wangon, District of Banyumas. Data collected by interview, observation, and documentation. This study found an association between the role of the Wali, the ancient mosque and shrine in the spread of Islam in the village Cikakak. Jaro Rajab ritual or grave pilgrimage or nyadran held every 26th of Rajab as a symbol of respect to KyaI Mustolih who spread Islam in the 17th century. Kyai Mustolih built Saka Tunggal Mosque in 1288 AD. Social practices of mutual assistance and cooperation is reflected in Jaro Rajab ritual performed in the tomb and mosque complex. Jaro Rajab ritual functioning as a unity element for communities and faiths.